Production of elastic Chitosan/Chondroitin sulphate multilayer films for tissue regeneration - Sousa, M. P. (2015)
Membrane-like scaffolds are suitable to induce regeneration in many and different anatomic sites, such as periodontal membrane, skin, liver and cardiac tissues. In some circumstances, the films should adapt to geometrical changes of the attached tissues, such as in cardiac or blood vessel tissue engineering applications. In this context, we developed stretchable two-dimensional multilayer constructs through the assembling of two natural-based polyelectrolytes, chitosan (CHT) and chondroitin sulphate (CS), using the layer-by-layer methodology. The morphology, topography and the transparency of the films were evaluated. The in- fluence of genipin, a natural-derived cross-linker agent, was also investigated in the control of the mechanical properties of the CHT/CS films. The water uptake ability can be tailored by changing the cross-linker concentration, which influenced the young modulus and ultimate tensile strength. The maximum extension tends to decrease with the increase of genipin concentration, compromising the elastic properties of CHT/CS films: nevertheless using lower cross-linker contents, the ultimate tensile stress is similar to the films not cross-linked but exhibiting a significant higher modulus. The in vitro biological assays showed better L929 cell adhesion and proliferation when using the crosslinked membranes and confirmed the non-cytotoxicity of the CHT/CS films. The developed free-standing biomimetic multilayer could be designed to fulfill specific therapeutic requirements by tuning properties such as swelling, mechanical and biological performances.